E Pluribus Octo – Building Consensus on Standards of Care and Experimentation in Cephalopod Research; a Historical Outlook - De Sio, Fabio; Hanke, Frederike D.; Warnke, Kerstin; Marazia, Chantal; Galligioni, Viola; Fiorito, Graziano; Stravidou, Ioanna; Ponte, Giovanna (Frontiers in Physiology, 2020)
The Directive 2010/63/EU “on the protection of animals used for scientific purposes” originally induced some concern among cephalopod researchers, because of the inclusion of cephalopod molluscs as the only invertebrates among the protected species. Here we reflect on the challenges and issues raised by Directive on cephalopod science, and discuss some of the arguments that provided support from the scientific community itself, to facilitate the implementation of the Directive 2010/63/EU in the scientific research context. A short overview of the aims of the COST Action FA1301 “CephsInAction”, serve as a paradigmatic instance of a pragmatic and progressive approach to respond to novel legislative concerns through community-building and expansion of the historical horizon. Between 2013 and 2017, the COST Action FA1301 has functioned as a hub for consolidation of the cephalopod research community, including about 200 representatives from 21 countries (19 European). Among its aims, CephsInAction promoted the collection, rationalisation and diffusion of knowledge relevant to cephalopods. In the supplementary information to this work, we present the translation of the first-published systematic set of guidelines on the care, management and maintenance of cephalopods in captivity (Grimpe, 1928), as an example of the potential advantages deriving from the confluence of pressing scientific concerns and historical interests.